Implementasi Program E-Filing Dalam Upaya Peningkatan Kepatuhan Wajib Pajak Orang Pribadi (Studi Pada Kantor Pelayanan Pajak Pratama Bojonegoro) - Abdurrohman, Sisilia (Jurnal Administrasi Publik, 2015)
Abstract: The Implementation of E-Filing Program for Compliance Improvement of Private Taxpayers (Study at Pratama Tax Service Office of Bojonegoro). Taxation modernization has been conducted by General Directorate of Tax in 2002. One step for taxation modernization is the improvement of business process and the development of information and communication technology. A form of the improvement of business process and the development of information and communication technology is e-Filing program that also represents e-Government. It seems that e-Filing is a method to deliver Annual Tax Report in electronic, online and real time ways through Internet by browsing into the website of Tax General Directorate (www.pajak.go.id). The implementation of e-Filing has been started in 2014. The implementation of e-Filing  is expected to improve the compliance of taxpayers in submitting Annual Tax Report. From research result, it is then concluded that steps of the implementation of e-Filing at KPP Pratama Bojonegoro have been consistent to the theories of procedural or managerial approaches to implementation. However, the implementation of e-Filing is not yet optimum to increase tax compliance. Keywords: tax modernization, e-government, e-filing, tax compliance   Abstrak: Implementasi Program E-Filing dalam Upaya Peningkatan Kepatuhan Wajib Pajak Orang Pribadi (Studi Pada Kantor Pelayanan Pajak Pratama Bojonegoro). Modernisasi perpajakan dilaksanakan oleh Direktorat Jenderal Pajak pada tahun 2002. Salah satu tahap dalam modernisasi perpajakan adalah perbaikan Business process dan teknologi informasi dan komunikasi. Salah satu wujud dari perbaikan business process dan teknologi informasi dan komunikasi adalah program e-Filing yang juga merupakan wujud penerapan e-Government. E-Filing merupakan suatu cara penyampaian SPT Tahunan secara elektronik yang dilakukan secara online dan real time melalui internet pada website Direktorat Jenderal Pajak (www.pajak.go.id). Implementasi e-Filing dimulai pada tahun 2014. Implementasi e-Filing ini di harapkan dapat berperan dalam meningkatkan kepatuhan wajib pajak dalam melaporkan SPT tahunan. Dari hasil penelitian dapat disimpulkan bahwa Langkah-langkah dalam implementasi e-Filing pada Kantor Pelayanan Pajak Pratama Bojonegoro telah sesuai dengan teori pendekatan prosedural atau manajerial dalam proses implementasi. Namun implementasi e-Filing belum berperan secara optimal dalam peningkatan kepatuhan pajak.   kata kunci: modernisasi perpajakan, e-government, e-filing, kepatuhan perpajakan